Penurunan Kadar Besi (Fe) Pada Air Tanah Dengan Menggunakan Cascade Aerator (Studi Air Tanah Universitas Riau) - Ricky Pribadi; Syarfi Daud; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Decreased levels of iron (Fe) in ground water still be a challenge, one of simple that can be applied to set aside the iron (Fe) content in the ground water that is aerated. This research aims to study the ability of cascade aerator in setting aside the iron content in ground water and calculate the value of coefficient of gas transfer. With the flow variation of 70, 80, 90 ml/s and time variation 120 minutes, 180 minutes and 240 minutes. The levels of Iron (Fe) before aeration is equal to 1,8 mg/l. The results of the research show the efficiency of the iron (Fe)content of the highest occurs at discharge of 90 ml/s and the best time 120 minutes with the efficiency value is equal to 94,4%. The value of the coefficient of gas transfer lines obtained in experiment 70 ml/s of 0,064/minutes.Keywords: aeration, cascade aerator, iron (Fe), flow, time, the coefficient of gas transfer (KLa)